Integrated soft start and safety shutdown - KRAMER DUSTIN; OPPER GREG; GOTKO DAN; BRUNSWIG CHARLES M; RIED DAVID L (2016)
The subject matter of this specification can be embodied in, among other things, a current control assembly that includes an electrical current flow path having a maximum current flow rate, a first current limiter in the electrical current flow path, the first current limiter comprising circuitry configured to adjustably restrict current flow along the electrical current flow path to a flow rate less than the maximum current flow rate in response to receipt of a first signal at a first input port, and a second current limiter in the electrical current flow path, the second current limiter arranged to interrupt the electrical current flow path in response to receipt of a second signal at a second input port. 除了其他事项之外，本规范的主题可具体化在电流控制组合件中，其包括具有最大电流流动速率的电流流动路径；在电流流动路径中的第电流限制器，该第电流限制器包括电路，电路配置成可调整地将沿着电流流动路径的电流流动限定到低于最大电流流动速率的流动速率，以响应在第输入端口处的第信号的接收；以及电流流动路径中的第二电流限制器，该第二电流限制器安排成中断电流流动路径，以响应在第二输入端口处的第二信号的接收。